PENINGKATAN PENGETAHUAN KADER POSYANDU KELURAHAN MARGASARI TERHADAP PENANGANAN STUNTING MELALUI PENCEGAHAN PERNIKAHAN ANAK DAN PENGENALAN MAQASHID SYARIAH - Nenny Kencanawati; Irianti Usman; Dwi Purliantoro; Dian Kusumawati; Ivonne Ayesha (UNIVERSITAS PGRI MADIUN, 2023)
Abstract. The purpose of this Community Service activity (PKM) is to provide enlightenment and deeper understanding for posyandu (Integrated Healthcare Center) cadres regarding the handling of stunting through preventing child marriage and implementing the purpose of life principles based on maqashid sharia (reasons behind the prohibitions and obligations stated in Islamic sharia). The activities were carried out in Margasari Village, at Jalan Cipagalo Girang Number 09, Buah Batu District, Bandung City. The implementation of this PKM activity was done through conducting lecture method given by two resource persons, followed by having a discussion as well as questions and answers sessions with the participants. The community service activities administered by the Muhammadiyah University of Bandung PKM team resulted in two conclusions, namely 1) Establishment of friendly relations with posyandu cadres and related cadres as the spearhead of stunting management. This condition makes it easier for the Muhammadiyah University of Bandung PKM team to understand and know the characteristics and behavioral patterns of cadres and people at risk of stunting in the effort to improve future stunting mitigation activities and programs. 2) Some of the participants were familiar with stunting, how ever did not know the ways to handle the condition properly. They did not have sufficient pre-marriage trainings such as best parenting practices; how to deal with household matters according to the true nature of life's purposes in accordance with the Maqashid sharia. Through the enlightenment delivered by the resource persons from the Muhammadiyah University of Bandung PKM Team, it is expected that the posyandu cadres possess sufficient knowledge in the purposes of life concept according to maqashid sharia to help create better and more effective future stunting prevention programs. Abstrak. Tujuan kegiatan Pengabdian Kepada Masyarakat (PKM) ini yakni untuk memberikan pencerahan dan pemahaman yang lebih mendalam kepada para kader posyandu, terkait penanganan stunting melalui pencegahan perkawinan anak dan penerapan maqashid syariah. Kegiatan PKM dilaksanakan di Keluarahan Margasari, Jalan Cipagalo Girang Nomor 09, Kecamatan Buah Batu, Kota Bandung. Pelaksanaan kegiatan PKM ini menggunakan metode ceramah atau penyampaian materi oleh dua orang narasumber, dan diskusi serta tanya jawab dengan para peserta. Kegiatan PKM yang dilaksanakan oleh Tim pengabdian Universitas Muhammdiyah ini menghasilkan dua simpulan, yaitu 1) Terjalinnya silaturahmi dengan para kader posyandu dan kader-kader terkait sebagai ujung tombak penanganan stunting. Kondisi ini memudahkan Tim PKM UMBandung dalam memahami dan mengetahui karakter serta perilaku kader dan masyarakat berisiko stunting guna melanjutkan kegiatan berikutnya. 2) Sebagian peserta telah mengenal stunting, namun belum mengetahui secara detail dan belum memahami cara penanganan secara tepat sejak pra nikah sampai penerapan berumah tangga dan mengasuh anak yang sesuai hakekat tujuan hidup sesungguhnya (Maqashid syariah). Melalui pencerahan yang disampaikan oleh narasumber dari Tim PKM UMBandung, pengetahuan para kader posyandu semakin meningkat, lebih terarah, dan efektif dalam membuat berbagai program penanggulangan stunting